Early treatment of class III malocclusion in primary dentition - Delesma-Chumbe, Angel (2015)
Class III malocclusion is the most complex to diagnose and treat, during the child’s growth is one of the most difficult challenges that the orthodontist can be found either in deciduous dentition, early mixed, late mixed or permanent. The goal of treatment of Class III malocclusion in primary dentition is to achieve a favorable environment for a better dentofacial development so this should be treated just malocclusion is diagnosed. In this article the case of a girl of 5 years 6 months with a skeletal class III malocclusion, negative overjet, 80% overbite, normodivergent pattern, is reported.